Ganancia de peso de juveniles de carpa herbívora (Ctenopharyngodon idella) alimentados con harina de soja micronizada - Montenegro, Luciano Federico (2021)
Summary: Inland aquaculture is one of the disciplines of animal production that has grown the most in recent years. As a consequence of the overexploitation of many marine fish stocks, organizations such as the FAO focused on promoting aquaculture of species of sweet water. In this sense, one of the most produced worldwide is grass carp (Ctenopharyngodon idella). Today, the diets of many freshwater species sweet contain in its formulation fishmeal as protein source, an input that raises production costs. From the foregoing, there is a need to investigate the replacement of said input by others, equally protein, that allow to maintain the expected weight gain, such as such as micronized soy flour which has a protein content greater than 40%. The objective of the present trial was to evaluate the gain of weight of juveniles of C. idella fed with flour of micronized soybeans. The use of micronized soybean flour constitutes a protein alternative that produces greater weight in the grass carp juveniles due to their high content protein. New formulations should be studied in which micronized soybean meal completely replaces the fishmeal.